An assessment of the Impact of Black Granite mining on sustainable development in Zimbabwe : the Case of Mutoko District from 2002 to 2017. - Chikuni, Witness (Midlands State University, 2020)
The concept of sustainable development has become a ubiquitous feature in most developmental policies across the breadth and length of the world. Therefore, this research analyzed the impact of the extraction of black granite on sustainable development particularly making use of the case of Mutoko District in Zimbabwe. Mining of black granite in Mutoko commenced way back in the early 1970s. The people in Mutoko District expected that the exploitation of the natural stone would bring sustainable development to the table and Mutoko, as a Growth Point, would be transformed into a town. However, this dream has failed to see the light of the day. The hypothesis of the research purported lack of congruent and decentralized legislative frameworks which govern the contact of black granite mining, as the major stumbling block against achieving sustainable development. The study examined the challenges faced in the extraction of black granite in Mutoko District. Both qualitative and quantitative methods were utilized during the process of collecting the research data. In tandem with the above, mixed methods of research analysis were also used to analyze the acquired data. For the qualitative analysis, both content analysis and thematic analysis were used whilst the Statistical Package for Social Sciences (SPSS) was used for quantitative analysis. Tables, graphs and pictures were utilized to substantiate and corroborate the facts raised and to enhance a more informative presentation of the acquired data. The acquired data managed to put into lime light the fact that lack of congruency within the legislative frameworks governing mining of black granite is the outstanding challenge whilst other problems include the deficiency of value addition, loss of land, siltation, high decibel noise pollution, destruction of cultural sites, spreading of diseases and sexual immorality, just to mention but a few. As an effort to mend the relationship between black granite mining and sustainable development, some remedial mechanisms were presented to include; the need to align the legislative frameworks governing mining of granite, giving more power to the local authorities to administer the exploitation and beneficiation of local resources, signing of Environmental Impact Assessment agreements and regularly social audits as well as Environmental Impact reviews.